2016
DOI: 10.1002/jcc.24522
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of relative free energies of binding using pre‐computed ensembles based on the single‐step free energy perturbation and the site‐identification by Ligand competitive saturation approaches

Abstract: Accurate and rapid estimation of relative binding affinities of ligand-protein complexes is a requirement of computational methods for their effective use in rational ligand design. Of the approaches commonly used, free energy perturbation (FEP) methods are considered one of the most accurate, though they require significant computational resources. Accordingly, it is desirable to have alternative methods of similar accuracy but greater computational efficiency to facilitate ligand design. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 64 publications
(100 reference statements)
2
45
0
Order By: Relevance
“…35 Follow-up studies showed that combining SSP with a ligand grid free energy approach offers a 1000-fold computational savings over traditional FEP for calculating the relative binding affinities once some upfront pre-computations are complete. 36 More recently, the method has been studied for bias 37 and applied to the efficient optimization of forcefields. 38 We expand on this SSP approach to perform computational fluorine scanning by comparing predictions from PFS for nine test systems to experimental data and to traditional alchemical calculations using FEP.…”
Section: Introductionmentioning
confidence: 99%
“…35 Follow-up studies showed that combining SSP with a ligand grid free energy approach offers a 1000-fold computational savings over traditional FEP for calculating the relative binding affinities once some upfront pre-computations are complete. 36 More recently, the method has been studied for bias 37 and applied to the efficient optimization of forcefields. 38 We expand on this SSP approach to perform computational fluorine scanning by comparing predictions from PFS for nine test systems to experimental data and to traditional alchemical calculations using FEP.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms are implicated in almost all cellular processes. FEP protocols have been previously used for studying interactions between PKs and ATP‐competitive ligands and rational design of PK inhibitors . It is possible to list merits of the FEP‐based protocol reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Applying Equation (1) with no intermediate states is referred to as single step perturbation (SSP) and this is the primary free energy method used in this work. Numerous studies have used SSP [16][17][18][19] , demonstrating that it is applicable to relative free energy calculations 20,21 and can be significantly faster than standard FEP 22 . Most recently, the authors of this paper have used SSP to perform computational fluorine scanning 23 .…”
Section: Introductionmentioning
confidence: 99%